Strategi Kebijakan Fiskal dalam Menunjang Pertumbuhan Ekonomi di Indonesia: Strategi Kebijakan Fiskal dalam Menunjang Pertumbuhan Ekonomi di Indonesia - Maftuha umu muhlisa; Dina novia amelia putri; Megawati nur sagita (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine how fiscal policy procedures from an Islamic point of view can support economic development in Indonesian. This research uses descriptive qualitative methodology and secondary data collection techniques from books, journals, and other sources. The effect of this research shows that fiscal strategy has a significant role in supporting the economic development of the Indonesian state. Fiscal policy refers to the behavior of the government to control revenues and expenditures and regulate taxes and public spending. Therefore, the government needs to pursue strategies through fiscal policy in an Islamic perspective in overcoming various problems and supporting economic growth in Indonesian.